(untitled) (International relations and international law Journal, 2016)
The concept of «global challenges» entered into a scientific revolution in the 60-70 years of the twentieth century, defined as problems that affect each person and humanity as a whole. This article discusses the causes and current problems of global food security in the context of concrete examples of agro-industrial complex of the Republic of Kazakhstan. As the main indicators characterizing food security adopted by the production and consumption of food per capita, imports of food and imported food consumption per capita and the level of security of the population of the Republic of the main types of food products. The main difficulties in the solution of global problems of food security are connected with huge additional costs of their decisions that won’t be coordinated with laws of the competition of decrease in expenses and receiving the maximum profit in the conditions of the market economy. Consequently, the solution of the contradiction between economic and social interests at all levels of managing are also made by contents of the solution of global problems of food security.